The results of diagnosis and treatment of chronic generalized catarrhal gingivitis in children at the background of chronic tonsillar infection - Yu. N. Koval; Zh. A. Novikova (Kazimierz Wielki University, 2017)
Biocenosis of sulcus in chronic generalized catarrhal gingivitis children (CGCG) without background pathology and with chronic tonsillitis (CH) has been investigated. Its development and clinical course depending on dominant microbial agent (streptococci or staphylococci) are specified. This expands  our knowledge about etiology and pathogenesis of CGCG. The results of local immunity and nonspecific resistance study in CGCG children with/ without contaminant pathology are given. A new method of the patients under study treatment has been worked out and clinically tested. It has been established that the use of the complex offered allowes to reduce a number of complications, relapses, and increases the general efficacy of treatment.